Incontinentia pigmenti - Motamedi Mohammad Hosein; Lotfi Ali; Azizi Taghi; Moshref Mohammad; Farhadi Sareh (Wolters Kluwer Medknow Publications, 2010)
Incontinentia pigmenti (IP) or Bloch-Sulzberger syndrome is a rare X-linked dominant genodermatosis related to the NF kappa B essential modulator (NEMO) gene with approximately 800 cases reported worldwide. It usually occurs in females characterized by cutaneous, skeletal, neurological, ocular and dental abnormalities as well as an increased risk of childhood malignancies. Herein, we report a case of IP in a 14-year-old girl emphasizing early diagnosis and adding to the current literature on the subject.